The Influence of Health Promotion Using Booklet Media About Tuberculosis on the Knowledge Level of Porters, Drivers, and Cleaning Service Staff at the Tjilik Riwut Airport Post, Working Area of Health Quarantine Center Class II Palangka Raya - Miana Chesaria Alvionesa; Riska Ovany; Merry Delyka (PROMOTOR, 2026)
According to secondary data from the WHO and the Ministry of Health, Tuberculosis (TB) remains one of the diseases with a high prevalence. Airports are convergence points for people from various regions and countries, making them high-risk locations for transmitting infectious diseases like TB. Therefore, primary prevention is needed to increase public knowledge at airports, particularly among porters, drivers, and cleaning service staff, which can be achieved through health promotion related to TB. Objective: To determine the influence of health promotion using booklet media about tuberculosis on the knowledge level of porters, drivers, and cleaning service staff at the Tjilik Riwut Airport post, working area of Health Quarantine Center Class II, Palangka Raya. Methods: This research employed a pre-experimental design, specifically a one-group pretest-posttest type. The sample consisted of 47 porters, drivers, and cleaning service staff at the Tjilik Riwut Airport post, selected through accidental sampling. The data analysis was conducted using the Wilcoxon test. Results: The Wilcoxon test results showed a p-value of 0.000 (p< 0.05), indicating a significant effect of health promotion about tuberculosis using booklet media on the knowledge level of porters, drivers, and cleaning service staff at the Tjilik Riwut Airport post, working area of Health Quarantine Center Class II Palangka Raya. Conclusion: This research concluded that health promotion using booklet media was proven effective in increasing the knowledge of porters, drivers, and cleaning service staff, as it encouraged workers to actively engage in literacy and information sharing actively, thereby enabling them to solve problems. It was recommended that partnerships be established with health facilities for the routine provision of health promotion regarding tuberculosis.